Roles of Major Chemokines in the Pathophysiology of Atrial Fibrillation - Saira Rafaqat; Fozia Bibi; Muhammad Aqib Murad; Huma Khurshid; Amna Sheerin (Cardiovascular Innovations and Applications)
Chemokines are a subclass of cytokines, a large family of small secreted proteins that communicate via G protein-coupled heptahelical chemokine receptors on the cell surface. Atrial fibrillation (AF) is the most prevalent clinically relevant cardiac rhythm condition. Patients with persistent AF have higher levels of C-X-C motif chemokine ligand 8 (CXCL8) than those with paroxysmal AF, thus suggesting a link between long-lasting AF and a low-grade inflammatory response. A newly identified function of C-X-C motif chemokine receptor 2 (CXCR2) is promoting monocyte infiltration of the atria, thus accelerating atrial remodeling and AF after hypertension. Elevated expression of C-X-C motif chemokine ligand 12 (CXCL12) and C-X-C motif chemokine receptor 4 (CXCR4) in the plasma or atria in patients with AF has been linked to increased atrial remodeling, prolonged hospital stays, and elevated risk of death. The CXCL12/CXCR4 axis is highly upregulated in patients with AF which and is among the most effective targets for AF prevention. Upregulated CXCR4 in patients with chronic AF and mitral valve disease is associated with atrial remodeling. Thus, chemokines may be involved in AF development.